Lexical and Semantic Transformations while Translating Texts from English (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the study of peculiarities of translating the English texts. It focuses on using the lexical and semantic transformations while translating texts from English into Ukrainian, investigates the factors that cause their appearance, determine  the influence of semantic context on meaning of a word or word-combination. The author analyzes the ways of obtaining the adequate translation according to the standards of Ukrainian language through using lexical and semantic replacements, paying attention to full equivalence of lexical units, partial equivalence, object and logic meaning, transposition of parts of speech, etc. Special concentration is paid to such lexical and semantic transformations as: concretization, generalization and modulation (semantic development). The author highlights the peculiarities of English vocabulary, which is more abstract than Ukrainian one.
Keywords: substitution; adequate translation; lexical unit; source language; target language; meaning of a word